Isokinetic evaluation in the upper limb amputee swimmer: a case report - Secchi, Leonardo Luiz Barretti; Muratt, Mavi Diehl; Saccol, Michele Forgiarini; Greve, Julia Maria D'Andrea (Acta Fisiátrica, 2009)
Swimming is one of the most popular sports studied, but swim-ming by athletes with physical disabilities suggests a new branch of research. Objective: To analyze muscle groups by isokinetic dynamometry: the adductor and abductor and the shoulder flexor and extensor of an elite Brazilian swimmer with an amputation at the level of the proximal third of the radius. Methods: The male patient was 18 years old, and had spent nine of those years competing. He was clinically evaluated via the functional DASH questionnaire and the EROE questionnaire on sports. The Biodex System 3 isokinetic dynamometer was used with the protocol of 5 repetitions at 60 ° / second, 20 repetitions at 180 º and 240 º / second as the movement of abduction / adduction and flexion / extension. Results: In the questionnaires there was no indication of pain or any other change in clinical evaluation. In the DASH questionnaire, the athlete reported a medium level of difficulty. His performance was excellent on the EROE scale. In isokinetic evaluation the athlete showed differences between the amputated side and the healthy side. Conclusion: Isokinetic evaluation is a good parameter to study the strength even in swimmers with physical disabilities, showing that these athletes need specific training.